Integrating strategies of chemistry, biochemistry and metabolomics for characterization of the medication principle of "treating cold/heat syndrome with hot/cold herbs". (15th July 2019) - Zhou, Ning; Yang, Yanyun; Li, Kai; Ke, Yingying; Zheng, Xiaoke; Feng, Weisheng; Bai, Zhiyao; Liu, Tong; Wang, Yangyang; Liu, Zhen; Li, Xingcan
Abstract: Ethnopharmacological relevance: "Treating cold syndrome with hot herbs & treating heat syndrome with cold herbs" is a fundamental medication principle of Chinese medicine. Scientists have been working hard to explore the scientific essence of this medication principle. However, researchers only focused on the herbs or syndrome individually, the intrinsic relationship between the cold/hot herbs and cold/heat syndrome received little attention. Consequently, the medication principle still lacked a scientific explanation. Aim of the study: The aim of present study was to explore the scientific essence involved in the medication principle. Materials and methods: First, extracts of cold and hot herb1-7 were analyzed using UPLC-Q-TOF/MS to research the chemical composition. Second, expression of enzymes relating glucose aerobic oxidation and respiratory chain were detected to assess the metabolic state of rats in cold herb, hot herb, cold syndrome and heat syndrome groups. Lastly, metabolomic approach was utilized to screen out biomarkers and related pathways shared between the cold and hot herb groups, the cold and heat syndrome groups, as well as the herb and syndrome groups. Results: The integrated results of chemistry, biochemistry and metabolomics study indicated that the cold (hot) herbs could remedy heat (cold) syndrome through inhibiting (promoting) arginine and proline metabolism and tryptophan metabolism, and the associated excessive (sluggish) material metabolism, ATP storage and generation in heat (cold) syndrome. The fundamental reason behind the differential efficacies of cold and hot herbs was the chemical composition and different contents of shared components. Conclusions: The medication principle was scientifically elucidated from perspective of material and energy metabolism. Moreover, this integrated novel strategy provides a feasible approach for future research of Chinese medicinal herb. Graphical abstract: Image 1 Highlights: "Treating cold/heat syndrome with hot/cold herbs" is a fundamental medication principle of Chinese medicine. Integrated results of chemistry, biochemistry and metabolomics clarified the scientific essence of the medication principle. The cold/hot herbs could remedy heat/cold syndrome through inhibiting/promoting arginine-proline and tryptophan metabolism. The fundamental reason behind the differential efficacies of cold and hot herbs was the chemical composition.